Variabilitas, Korelasi, dan Analisis Kelas Sepuluh Genotipe Nilam (Pogostemon cablin Benth.): Variabilitas, Korelasi, dan Analisis Kelas Sepuluh Genotipe Nilam (Pogostemon cablin Benth.) - Sri Nurmayanti; M Tahir; Gusti Ayu Putu Dianti (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Patchouli is a plant that produces essential oils that cannot be substituted with other essential oils. The genetic diversity of patchouli is low, because in Indonesia there are only five superior clones, and this is caused a limitation for cultivation. Therefore it is necessary to produce new superior clones filled by national standards. This study tested nine patchouli superior genotypes resulting from mutations. The main objective of this research were to obtain the results stability, wide variability, to determine the correlation of each parameter and class closeness among ten patchouli genotypes. The study used nine plant clones of patchouli from the collection and one patchouli variety released in Indonesia as a comparison, namely Lhoksemauwe. The treatments were arranged in a completely randomized block design with three replications. Based on the results of the study, there was no significant difference in almost all observed parameters except for the stem diameter parameter. The genotype used has shown the stability of the results at the Rajabasa location in South Lampung. The variability in almost all parameters showed broad criteria, except for the parameters of cell turgidity and oil yield. Significant positive correlations occurred between several observed parameters. There are four classes formed and three of it have more than 90% closeness.